Local water bridges and protein conformational stability. - Petukhov, M. (Cold Spring Harbor Laboratory Press, 1999)
Recent studies have pointed out the important role of local water structures in protein conformational stability. Here, we present an accurate and computationally effective way to estimate the free energy contribution of the simplest water structure motif--the water bridge. Based on the combination of empirical parameters for accessible protein surface area and the explicit consideration of all possible water bridges with the protein, we introduce an improved protein solvation model. We find that accounting for water bridge formation in our model is essential to understand the conformational behavior of polypeptides in water. The model formulation, in fact, does not depend on the polypeptide nature of the solute and is therefore applicable to other flexible biomolecules (i.e., DNAs, RNAs, polysaccharides, etc.).